Studi Deskriptif Pelaksanaan Pembelajaran IPS di Kelas Alam Pada Kelas V B Sekolah Dasar Alam Mahira - Pratiwi Agustina; Wurdjinem Wurdjinem; Abdul Muktadir (Universitas Bengkulu, 2018)
This study aims to describe the implementation of IPS learning in thenatural classroom in class V B Elementary School Mahira Bengkulu.This research is a qualitative research. The research subjects are VBgrade teachers and VB class students. The research instrument is theresearcher itself using observation sheets, interviews and documentation.Data collection techniques use observation guidelines, interviews anddocumentation. Data analysis techniques are data collection, datareduction, data presentation, and conclusion drawing. The technique ofdata validity through prolongation of observation, increasing persistenceand triangulation. The results showed that the teacher did the planningstages of making Lesson Plan and Creating a Daily Plan. At theimplementation stage, the teacher does not deliver the learning objectives,does not convey the scope of the learning material, does not introduce thenatural class, does not facilitate the students in summarizing thematerial. Based on the result of the research, it can be concluded that theVB class teacher has not adjust the planning with the implementation, inthe implementation of the teacher does not convey the purpose of learning,conveying the material coverage, introducing the nature class, difficult toorganize the students and not concluding the learning. In the evaluationof the teacher did not make the format of the assessment.Keywords: IPS Learning, Outdoor Classroom